2012
DOI: 10.1590/s1516-89132012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab treatment prevents hyperglycemia and the intensification of hepatic gluconeogenesis in an animal model of high fat diet-induced liver glucose overproduction

Abstract: The effect of infliximab on gluconeogenesis in an animal model of diet-induced liver glucose overproduction was investigated. The mice were treated with standard diet (SD group) or high fat diet (HFD group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similar results were also found by Gonzalez-Gay et al ( 339 ) in insulin resistant patients, with RA ( Table II ). In addition, Haida et al ( 340 ) demonstrated that infliximab treatment prevents hyperglycemia and liver gluconeogenesis, in high fat diet-fed mice. Moreover, infliximab seems to ameliorate TNF-α-induced IR, in 3T3-L1 adipocytes, in vitro , by improving the insulin signaling pathway, via inhibition of protein tyrosine phosphatase 1B ( 341 ).…”
Section: Therapeutic Interventions On Inflammatory Mediators For the ...mentioning
confidence: 99%
“…Similar results were also found by Gonzalez-Gay et al ( 339 ) in insulin resistant patients, with RA ( Table II ). In addition, Haida et al ( 340 ) demonstrated that infliximab treatment prevents hyperglycemia and liver gluconeogenesis, in high fat diet-fed mice. Moreover, infliximab seems to ameliorate TNF-α-induced IR, in 3T3-L1 adipocytes, in vitro , by improving the insulin signaling pathway, via inhibition of protein tyrosine phosphatase 1B ( 341 ).…”
Section: Therapeutic Interventions On Inflammatory Mediators For the ...mentioning
confidence: 99%
“…[1][2][3][4][5][6] Taking into account that the typical diet of Western countries is high in fat, 7,8 mice fed with HFD provide a model that more accurately represents the typical human diet compared with models where mice are fed with a balanced standard chow. [12][13][14] However, there are few studies regarding the effects of dietary enrichment with ɷ-3 polyunsaturated fatty acid [linseed oil (LO)] or ɷ-9 monosaturated fatty acid [macadamia oil (MO)] on the metabolic changes induced by HFD. 9,11 This HFD experimental model was also shown to be suitable to demonstrate the possibility to prevent or reverse the metabolic changes induced by an HFD.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 This HFD experimental model was also shown to be suitable to demonstrate the possibility to prevent or reverse the metabolic changes induced by an HFD. [12][13][14] However, there are few studies regarding the effects of dietary enrichment with ɷ-3 polyunsaturated fatty acid [linseed oil (LO)] or ɷ-9 monosaturated fatty acid [macadamia oil (MO)] on the metabolic changes induced by HFD. 15,16 Moreover, to the best of our knowledge, the impact of LO and MO in the hyperglycaemic state and liver glucose overproduction induced by an HFD in mice has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A link between inflammation and insulin resistance has been proposed in recent years . In animal models, inhibition of TNF‐α, a major pro‐inflammatory cytokine, decreases insulin resistance and reduces hepatic gluconeogenesis . Non‐diabetic, non‐obese patients with inflammatory bowel disease treated with TNF‐α inhibitors exhibited a significant reduction in insulin, C‐peptide and insulin resistance index .…”
mentioning
confidence: 99%